THE EFFECT OF SIMULATION TECHNIQUE TOWARD STUDENTS’ SPEAKING SKILL - I Made Permadi Utama (Universitas Pendidikan Mandalika, 2015)
This research is aimed to find out the effect of Simulation Technique towards Students’ Speaking Skill at the second semester students of FPBS IKIP Mataram. The sample of this research is the second semester students of FPBS IKIP Mataram. The sample took by using simple random sampling. As the result of the sampling process, A class as experimental group and B class as control group. The research was quasi experimental with pre-test and post-test design. The technique that was used to analyze the data were descriptive and inferential statistic. The finding of the research shows that mean score of experiment group higher than control group and the score of t-test (2. 90) is higher than tt (2.021) from (df) in degree of significance 0.05%. So, it can be concluded that there are any significance effect of Simulation Technique towards Students’ Speaking Skill at the second semester students of FPBS IKIP Mataram.